Epoxy resin containing symmetric phosphorus-nitrogen flame retardant and method for preparing the same

CN121801051BActive Publication Date: 2026-10-16QINGDAO UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202512020922.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-30
Publication Date
2026-10-16
Estimated Expiration
2045-12-30

AI Technical Summary

Technical Problem

[0004]现有环氧树脂阻燃改性技术普遍存在三大核心缺陷:一是阻燃剂添加量与基体性能平衡矛盾,高添加量体系易破坏EP力学与加工性能,低添加量体系则常缺失介电、抑烟等关键性能;二是多性能协同性不足,多数体系难以同时兼顾阻燃、抑烟、介电优化与力学提升,存在明显性能短板;三是分子结构设计欠缺精准性,非对称结构或固有偶极矩易引发界面极化,且阻燃剂与基体界面相容性调控不足,限制性能优化上限

Benefits of technology

1.本发明通过HMT与TPP反应合成对称型磷氮阻燃剂MTTP,利用磷-氮协同作用实现高效阻燃。仅添加2wt.%的MTTP即可使环氧树脂达到UL-94 V-0等级,极限氧指数(LOI)提升至31.5%,相较于纯环氧树脂(LOI=24.0%,无UL-94等级)阻燃效果大幅改善;同时,总热释放(THR)降低8.7%,总烟量(TSP)下降31.6%,有效解决了传统环氧树脂易燃、燃烧时产烟量大的核心问题,且在低添加量下的阻燃效率优于现有多数含P-N结构的阻燃改性环氧树脂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121801051B_ABST
    Figure CN121801051B_ABST
Patent Text Reader

Abstract

The application discloses an epoxy resin containing symmetrical phosphorus-nitrogen flame retardant and a preparation method thereof, and relates to the technical field of epoxy resins.The technical scheme is as follows: after mixing an epoxy resin, a symmetrical phosphorus-nitrogen flame retardant and a curing agent, the mixture is cured to obtain the epoxy resin containing the symmetrical phosphorus-nitrogen flame retardant; the preparation method of the symmetrical phosphorus-nitrogen flame retardant is as follows: hexahydro-1,3,5-tris(hydroxyethyl)-s-triazine, triphenyl phosphate and a catalyst are reacted at 140-180 DEG C for 2-5 h, and the product is distilled under reduced pressure to obtain the symmetrical phosphorus-nitrogen flame retardant.The symmetrical phosphorus-nitrogen flame retardant (MTTP) is synthesized by the reaction of TPP and HMT, and is applied to the epoxy resin, so that the flame-retardant performance and dielectric performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of epoxy resin technology, specifically to an epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant and its preparation method. Background Technology

[0002] Epoxy resin (EP) is widely used in electrical, construction, transportation, and aerospace fields due to its excellent mechanical properties, good thermal stability, outstanding electrical insulation properties, and strong adhesion. Particularly in the electrical field, epoxy resin is widely used for potting and protecting electronic components and insulating electrical equipment. However, epoxy resin is composed of flammable elements such as carbon, hydrogen, and oxygen, making it highly flammable and generating heat and smoke, posing a significant threat to human life.

[0003] Adding flame retardants to EP (Effective Flame Retardant) is the most common and economical method. Traditional halogenated flame retardants are gradually being phased out, while phosphorus-based flame retardants are considered one of the most promising types of flame retardants due to their environmentally friendly properties and high flame retardancy. Meanwhile, nitrogen, as an effective flame-retardant synergist, has been extensively studied. For example, Ai et al. synthesized VDSiNP containing flexible chains and rigid functional groups of P / N / Si elements. EP / VDSiNP9 passed the V-0 level test, with a limiting oxygen index (LOI) of 34.3%. Compared with pure EP, the dielectric constant was reduced by 25.3% and the dielectric loss was reduced by 41.2% ([1] Jixiang A, Lanlan W, Xiao W, et al. Synthesis of a novel P / N / Si-containing bio-based flame retardant for fire-safe, tough, and low-dielectric epoxy resin[J]. Materials Today Chemistry, 2025, 47102790-102790.DOI:10.1016 / J.MTCHEM.2025.102790.). Wang et al. synthesized a phosphorus / nitrogen-containing compound DOPO-BAPh. The modified EP achieved a LOI value of 35.8% with a phosphorus loading of only 0.26 wt.%, and obtained a V-0 rating in the UL-94 test ([2] Donghui W, Quanyi L, Xiaoliang P, et al. High-efficiency phosphorus / nitrogen-containing flame retardant on epoxy resin[J]. Polymer Degradation and Stability, 2021, 187109544-.DOI:10.1016 / J.POLYMDEGRADSTAB.2021.109544.).Wang et al. synthesized a reactive bio-based P / N flame retardant (VTP). 5 wt.% VTP enabled EP to reach the UL-94V-0 rating, increased the LOI value to 30.5%, and reduced the peak heat release (PHRR) by 36.1% and the total smoke output (TSP) by 37.9%, respectively ([3]Yadong W, Liyan L, Li M, et al. Transparent,flame retardant, mechanically strengthened and low dielectric EP composites enabled by a reactive bio-based P / N flame retardant[J]. Polymer Degradation and Stability,2022,204DOI:10.1016 / J.POLYMDEGRADSTAB.2022.110106.).

[0004] Existing epoxy resin flame retardant modification technologies generally suffer from three major defects: First, there is a contradiction between the amount of flame retardant added and the matrix properties. High addition levels easily damage the mechanical and processing properties of epoxy resin (EP), while low addition levels often lack key properties such as dielectric properties and smoke suppression. Second, there is insufficient synergy among multiple properties. Most systems cannot simultaneously achieve flame retardancy, smoke suppression, dielectric optimization, and mechanical improvement, resulting in significant performance shortcomings. Third, the molecular structure design lacks precision. Asymmetric structures or inherent dipole moments easily induce interfacial polarization, and the compatibility between the flame retardant and the matrix interface is not well controlled, limiting the upper limit of performance optimization. Therefore, there is an urgent need to develop new epoxy resin flame retardant modification technologies to overcome the above-mentioned defects in existing technologies. Summary of the Invention

[0005] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide an epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant and its preparation method. A symmetrical phosphorus-nitrogen flame retardant (MTTP) is synthesized by reacting TPP with HMT and then applied to epoxy resin. By using a low addition amount, the drawback of high load is overcome. The dipole moment is reduced to zero by relying on the symmetrical rigid molecular structure. This not only solves the problem of aggravated smoke release in the traditional PN system, but also simultaneously optimizes the flame retardant properties, dielectric properties and mechanical toughness of the material. At the same time, the interfacial compatibility is enhanced by non-covalent bond interactions such as hydrogen bonding and π-π stacking, thus comprehensively making up for the shortcomings of the prior art and achieving a synergistic improvement of multiple properties.

[0006] The technical solution of this invention is as follows: On one hand, the present invention provides a method for preparing an epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant, wherein the epoxy resin, the symmetrical phosphorus-nitrogen flame retardant and the curing agent are mixed and cured to obtain an epoxy resin containing the symmetrical phosphorus-nitrogen flame retardant; wherein the preparation method of the symmetrical phosphorus-nitrogen flame retardant is as follows: hexahydro-1,3,5-tris(hydroxyethyl)-s-triazine (HMT), triphenyl phosphate (TPP) and a catalyst are reacted at 140-180°C for 2-5 hours, and the product is distilled under reduced pressure to obtain the symmetrical phosphorus-nitrogen flame retardant.

[0007] Preferably, the curing agent is 4,4'-diaminodiphenylmethane (DDM).

[0008] Preferably, the epoxy resin accounts for 78.4-79.2% of the total mass of the raw materials, the symmetrical phosphorus-nitrogen flame retardant accounts for 1-2% of the total mass of the raw materials, and the curing agent accounts for 19.6-19.8% of the total mass of the raw materials.

[0009] Preferably, the specific operation process for preparing epoxy resin containing symmetrical phosphorus-nitrogen flame retardant is as follows: the epoxy resin and the symmetrical phosphorus-nitrogen flame retardant are mixed and stirred at 100-140°C, and then a curing agent is added to obtain a mixture; the mixture is poured into a preheated mold and placed in a vacuum oven to remove air bubbles; and cured at 110-160°C for 2-4 hours to obtain epoxy resin containing symmetrical phosphorus-nitrogen flame retardant.

[0010] Preferably, the catalyst is sodium hydroxide.

[0011] Preferably, the molar ratio of hexahydro-1,3,5-tris(hydroxyethyl)-s-triazine, triphenyl phosphate, and catalyst is (0.03-0.06):(0.14-0.18):(0.02-0.05).

[0012] Preferably, the vacuum distillation temperature is 140-180℃ and the time is 2-6 hours.

[0013] On the other hand, the present invention provides an epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant, which is prepared by the above-described method for preparing an epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant.

[0014] Compared with the prior art, the present invention has the following advantages: 1. This invention synthesizes the symmetrical phosphorus-nitrogen flame retardant MTTP through the reaction of HMT and TPP, achieving high-efficiency flame retardancy through the synergistic effect of phosphorus and nitrogen. Adding only 2 wt.% MTTP can enable epoxy resin to achieve the UL-94 V-0 rating, increasing the limiting oxygen index (LOI) to 31.5%, a significant improvement in flame retardancy compared to pure epoxy resin (LOI=24.0%, no UL-94 rating). Simultaneously, the total heat release (THR) is reduced by 8.7%, and the total smoke production (TSP) decreases by 31.6%, effectively solving the core problems of traditional epoxy resins' flammability and high smoke production during combustion. Furthermore, the flame retardant efficiency at low addition levels is superior to most existing flame-retardant modified epoxy resins containing a PN structure.

[0015] 2. The epoxy resin composite material prepared by this invention exhibits excellent dielectric properties in high-frequency electronic applications. When the MTTP addition amount is 1 wt.%, the composite material exhibits excellent dielectric properties at 10... 7 The dielectric constant at Hz is as low as 3.32, which is lower than that of pure epoxy resin (3.42), and the dielectric constant decreases significantly in the low-frequency range. At the same time, when the MTTP addition is 1wt.% or 2wt.%, the dielectric loss is significantly lower than that of pure epoxy resin in the low-frequency range and remains stable in the high-frequency range. This meets the requirements of electronic device packaging for low dielectric constant and low dielectric loss, ensures the speed and stability of signal transmission, and overcomes the defect of dielectric performance deterioration after the addition of some flame retardants.

[0016] 3. In this invention, the introduction of MTTP enhances the mechanical properties of epoxy resin through multiple effects. After adding 2 wt.% MTTP, the composite material exhibits a flexural strength of 96.9 MPa (approximately 8.6% higher than pure EP), a tensile strength of 58.0 MPa (approximately 33.6% higher than pure EP), and an elongation at break increasing from 1.5% to 5.5%, significantly improving tensile toughness. Simultaneously, the peel strength increases by approximately 6.3%, meeting the requirements for component fixation and performance stability in electronic packaging. Molecular dynamics simulations and SEM analysis confirm that stable hydrogen bonds are formed between MTTP and epoxy resin molecular chains, enhancing π-π stacking, reducing molecular chain mobility, and forming uniform microcracks on the fracture surface, effectively absorbing impact energy and achieving simultaneous optimization of strength and toughness.

[0017] 4. Although the addition of MTTP reduces the initial decomposition temperature (T) of the composite material. 5% While the calorific value decreased slightly, the residual char content at 800℃ significantly increased through catalytic carbonization. Specifically, the residual char rate reached 16.9% with 1 wt.% MTTP addition (a 67.3% increase compared to pure EP). The resulting dense carbon layer effectively blocked heat and oxygen transfer. Simultaneously, the glass transition temperature (T0) decreased. g The concentration of MTTP increases with increasing MTTP content; at an addition of 2 wt.%, T... gReaching 150.4℃, it improves the stability of the material in high-temperature environments and balances the synergistic relationship between flame retardancy and thermal performance.

[0018] 5. The addition of MTTP makes the epoxy resin molecular chains more tightly bonded, increasing the water contact angle of the composite material from 77.98° of pure EP to 79.81°, slightly enhancing hydrophobicity and helping to improve the electrical insulation stability of the material in humid environments. At the same time, the composite material maintains a certain degree of transparency, allowing clear observation of the internal structure of electronic components, facilitating subsequent fault diagnosis and status monitoring without disassembling and damaging the product, thus improving convenience in practical applications.

[0019] 6. The flame retardant synthesis and epoxy resin composite process of the present invention is simple, the reaction conditions are mild, and no complex equipment is required; all raw materials used are commercially available products, the amount of flame retardant added is low, no additional toxic and harmful components are required, which meets environmental protection requirements, and at the same time reduces the cost and threshold of industrial production, and has good application prospects. Attached Figure Description

[0020] Figure 1 These are standard diagrams of the raw materials and products in Example 1 of this invention, wherein (a) is a schematic diagram of the preparation method of the symmetrical phosphorus-nitrogen flame retardant MTTP-A; (b) are FTIR spectra of TPP, HMT, and MTTP-A; and (c) are FTIR spectra of TPP, HMT, and MTTP-A. 1 HNMR; (d) for TPP and MTTP-A 31 PNMR spectrum; (e) TGA and DTG curves of MTTP-A; (f) Simulation of electrostatic potential energy of MTTP-A.

[0021] Figure 2 These are standard diagrams of the raw materials and products in Example 2 of this invention, wherein (a) is a schematic diagram of the preparation method of the symmetrical phosphorus-nitrogen flame retardant MTTP-B; (b) are FTIR spectra of TPP, HMT, and MTTP-B; and (c) are FTIR spectra of TPP, HMT, and MTTP-B. 1 HNMR; (d) for TPP and MTTP-B 31 PNMR spectrum.

[0022] Figure 3 These are standard diagrams of the raw materials and products in Example 3 of the present invention, wherein (a) is a schematic diagram of the preparation method of the symmetrical phosphorus-nitrogen flame retardant MTTP-C; (b) are FTIR spectra of TPP, HMT, and MTTP-C; and (c) are FTIR spectra of TPP, HMT, and MTTP-C. 1 HNMR; (d) for TPP and MTTP-C 31 PNMR spectrum.

[0023] Figure 4These are test graphs of the thermal and dielectric properties of EP / MTTP-1%, EP / MTTP-2%, and EP in Embodiment 4 of the present invention, wherein (a) is the TGA curve of EP / MTTP-1%, EP / MTTP-2%, and EP under N2; (b) is the DTG curve of EP / MTTP-1%, EP / MTTP-2%, and EP; (c) is the DSC test curve of EP / MTTP-1%, EP / MTTP-2%, and EP; (d) is the breakdown field strength of EP / MTTP-1%, EP / MTTP-2%, and EP; (e) is the dielectric loss of EP / MTTP-1%, EP / MTTP-2%, and EP; and (f) is the dielectric constant of EP / MTTP-1%, EP / MTTP-2%, and EP.

[0024] Figure 5 This is a test chart of the flame retardancy of EP / MTTP-1%, EP / MTTP-2%, and EP according to Embodiment 4 of the present invention, wherein (a) is the LOI data and UL-94 results of EP / MTTP-1%, EP / MTTP-2%, and EP; (b) is a comparison chart of LOI of EP / MTTP-2% with other existing materials; (c) is the THR test chart of EP / MTTP-1%, EP / MTTP-2%, and EP; (d) is the TSP of EP / MTTP-1%, EP / MTTP-2%, and EP; (e) is the mass loss curve of EP / MTTP-1%, EP / MTTP-2%, and EP; (f) is the HRR test chart of EP / MTTP-1%, EP / MTTP-2%, and EP; (g) is the SPR test chart of EP / MTTP-1%, EP / MTTP-2%, and EP; (h) is a comparison chart of TSP of EP / MTTP-2% with other existing materials; and (i) is a comparison chart of TSP reduction rate of EP / MTTP-2% with other existing materials.

[0025] Figure 6 These are digital photographs and scanning electron microscope images of carbon residues after CCT testing of EP / MTTP-1%, EP / MTTP-2%, and EP in Example 4 of this invention, wherein (a), (a'), (a''), and (a''') correspond to EP, (b), (b'), (b''), and (b''') correspond to EP / MTTP-1%, and (c), (c'), (c''), and (c''') correspond to EP / MTTP-2%.

[0026] Figure 7The XPS results of the carbon residue after CCT testing of EP / MTTP-2% and EP in Example 4 of this invention are shown in (a) and (b), which are the full XPS spectra of carbon residue after CCT testing of EP / MTTP-2% and EPCCT; (c) is the C 1s spectrum of EP; (d) is the N 1s spectrum of EP; (e) is the C 1s spectrum of EP / MTTP-1%; (f) is the N 1s spectrum of EP / MTTP-1%; and (g) is the P 2p spectrum of EP / MTTP-1%.

[0027] Figure 8 These are thermal decomposition test graphs of EP / MTTP-1%, EP / MTTP-2%, and EP in Example 4 of the present invention, where (a) and (b) are TG-FTIR thermograms of EP and EP / MTTP-2%, respectively; (c) and (d) are FTIR spectra of the pyrolysis products of EP and EP / MTTP-2% at different temperatures, respectively; and (e)-(i) are the intensity curves of aromatic compounds, carboxyl compounds, CO, CO2, and hydrocarbons of EP and EP / MTTP-2% as a function of time, respectively.

[0028] Figure 9 These are mechanical property test graphs of EP / MTTP-1%, EP / MTTP-2%, and EP according to Embodiment 4 of the present invention, wherein (a) is the bending strength; (b) is the tensile strength and elongation at break; (c) is the average peel force and average peel strength of EP / MTTP-1%, EP / MTTP-2%, and EP; (d) is the cohesive energy density; (e) is the mean square displacement curve; (f) is the radial distribution function curve; and (g)-(i) are SEM images of the tensile fracture surfaces of EP, EP / MTTP-1%, and EP / MTTP-2%, respectively.

[0029] Figure 10 These are hydrophobicity and transparency test images of EP / MTTP-1%, EP / MTTP-2%, and EP according to Embodiment 4 of the present invention, wherein (a)-(c) are water contact angle photographs of EP, EP / MTTP-1%, and EP / MTTP-2%, respectively; (d) is the contact angle of EP / MTTP-1%, EP / MTTP-2%, and EP; and (e)-(g) are the transparency of EP, EP / MTTP-1%, and EP / MTTP-2%, respectively. Detailed Implementation

[0030] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention.

[0031] The raw materials used in the following examples are sourced from the following sources: Epoxy resin: Epoxy value 0.51 mol / 100g, Nantong Xingchen Synthetic Materials Co., Ltd.

[0032] DDM, HMT, TPP: Aladdin Reagents (Shanghai) Co., Ltd.

[0033] Sodium hydroxide: Sinopharm Chemical Reagent Co., Ltd.

[0034] The characterization and performance testing methods in the embodiments are as follows: Fourier transform infrared (FT-IR) spectroscopy analysis was performed using a Nicolet-IS10 Fourier transform infrared spectrometer, with a scanning range of 4000-400 cm⁻¹. -1 .

[0035] Thermogravimetric analysis (TGA) was performed using a TGDTA6300 analyzer in a nitrogen atmosphere at a heating rate of 10 °C / min and a flow rate of 20 mL / min, with a temperature range of 40–700 °C.

[0036] Thermogravimetric infrared spectroscopy (TG-IR) was performed using a TGA 4000 analyzer under a nitrogen atmosphere at a heating rate of 10 °C / min and a flow rate of 50 mL / min. Fourier transform infrared spectroscopy (FTIR) was performed using a Spectrum Two Fourier transform infrared spectrometer with a scanning range of 4000–500 cm⁻¹. -1 .

[0037] The glass transition temperature (Tg) was determined using a TA-DSC2500 differential scanning calorimeter. g The test temperature range was 20-200℃, and the heating rate was 20℃ / min.

[0038] The tensile and flexural strengths of EP / MTTP -1%, EP / MTTP -2%, and EP were tested using a universal testing machine (RMES-100B). Tensile tests were performed at a speed of 10 mm / min, and flexural tests at a speed of 2 mm / min, according to ASTM D638 and ASTM D790 standards.

[0039] The flame retardancy of EP / MTTP -1%, EP / MTTP -2%, and EP was tested using the limiting oxygen index (LOI) and a vertical flame tester. Sample dimensions were set to 100 × 6.5 × 3.2 mm according to ASTM D2863-10 and ASTM D3801-10, respectively. 3 and 130×13×3.2mm 3 .

[0040] The combustion performance of EP / MTTP -1%, EP / MTTP -2%, and EP was tested using a cone calorimeter (CCT), with a VOUCH 6810 simulating 35 kW / m³. 2 Combustion behavior of EP / MTTP -1%, EP / MTTP -2%, and EP under thermal radiation, according to ASTM E1354, with sample size of 100×100×3mm. 3 .

[0041] Using a Concept 40 dielectric impedance-thermal shock current analyzer, at room temperature and a frequency range of 1Hz-10MHz, the dielectric constant and dielectric loss of EP / MTTP -1%, EP / MTTP -2%, and EP were measured. The sample size was 40×40×2mm. 3 .

[0042] X-ray photoelectron spectroscopy (XPS) was performed using Thermo Scientific K-Alpha to detect the residues of EP / MTTP -1%, EP / MTTP -2%, and EP after CCT.

[0043] Following the CCT test, the carbon residues of EP / MTTP-1%, EP / MTTP-2%, and EP were analyzed using a JEOL-JSM-6700F scanning electron microscope (SEM).

[0044] The contact angle was measured using the YIKE-360A contact angle tester manufactured by Chengde Yike Test Instrument Factory, and the water contact angles of EP / MTTP-1%, EP / MTTP-2%, and EP were obtained.

[0045] The adhesion properties of EP / MTTP-1%, EP / MTTP-2%, and EP were evaluated using a 90° tear test conducted on a universal testing machine (RMES-100B). The adhesion interface consisted of 25×25 mm surfaces. 2 The composition and tearing speed are set to 50 mm / min.

[0046] Example 1 The preparation method of the symmetrical phosphorus-nitrogen flame retardant in this embodiment is as follows: Figure 1 As shown in (a), firstly, HMT (10.96 g, 0.050 mol) and TPP (50.57 g, 0.155 mol) were added to a three-necked flask, and 1.23 g of sodium hydroxide (0.031 mol) was added. The mixture was reacted at 150 °C for 4 h to obtain a yellowish-brown liquid. Subsequently, the product was poured into a rotary evaporator and evaporated under reduced pressure at 140 °C for 3 h. By removing small molecules, a clear liquid was obtained, which is the symmetrical phosphorus-nitrogen flame retardant, denoted as MTTP-A.

[0047] Figure 1 (b) The chemical structures of MTTP-A, TPP, and HMT are shown, and these structures were characterized by FTIR spectroscopy. It can be seen that the peak of the benzene ring in TPP appears at 1494 cm⁻¹. -1 and 1595cm -1 The same characteristic peak also appeared in MTTP-A. Furthermore, a peak at 1290 cm⁻¹ was observed in the FTIR spectrum of MTTP-A. -1 The peak at 1022 cm⁻¹ belongs to P=O. -1 and 960cm -1 The peak at 1247 cm⁻¹ is attributed to POC. Furthermore, a peak at 1247 cm⁻¹ was also observed in the FTIR spectrum of MTTP-A. -1 The peak at which CN is attributed to the nitrogen-containing hexagonal triazine ring in HMT is located.

[0048] Figure 1 (c) Demonstrates MTTP-A, TPP, and HMT. 1 1H NMR spectra. For the MTTP-A spectrum, the signal in the 7–8.01 ppm range is attributed to hydrogen in the benzene ring, and these signals overlap with those of TPP. For the HMT spectrum, the signal at 4.75 ppm is attributed to the -OH in -CH2-OH, which does not correspond in the MTTP-A spectrum, indicating that the transesterification reaction has proceeded sufficiently; the signal in the 3.25–3.75 ppm range is attributed to H in N-CH2-CH2-O, while the signal in the 2.5–3 ppm range is attributed to H in N-CH2-N of the hexahydrotriazine ring, and these signals overlap with those of MTTP-A. Figure 1 (d) shows the MTTP-A and TPP. 31 P NMR spectrum. The signal at -17.25 ppm is attributed to P in TPP. After the transesterification reaction, the signal of P in MTTP-A shifts to -11.55 ppm.

[0049] Figure 1 (e) shows the TGA and DTG curves of MTTP-A, and the initial decomposition temperature of MTTP-A (T). 5% The temperature at which the maximum decomposition rate is 171.4℃ is the highest. max The temperature of MTTP-A is 286.5℃, which is lower than that of EP, indicating its potential to prevent EP combustion. Furthermore, the charge distribution of MTTP-A was analyzed, such as... Figure 1As shown in (f). The results show that MTTP-A has a dipole moment of 0 and contains three strongly electronegative P=O groups and six strongly electronegative benzene rings. Furthermore, the P=O groups enable MTTP-A to act as electron donors. Therefore, it is hypothesized that MTTP-A particles are compatible with the EP chain through a polarity-matching effect, and that MTTP-A exhibits almost no molecular polarization.

[0050] Example 2 The preparation method of the symmetrical phosphorus-nitrogen flame retardant in this embodiment is as follows: Figure 2 As shown in (a), firstly, HMT (10.96 g, 0.050 mol) and TPP (53.51 g, 0.164 mol) were added to a three-necked flask, and 1.6 g of sodium hydroxide (0.04 mol) was added. The mixture was reacted at 160 °C for 5 h to obtain a yellowish-brown liquid. Subsequently, the product was poured into a rotary evaporator and evaporated under reduced pressure at 160 °C for 5 h. By removing small molecules, a clear liquid was obtained, which is the symmetrical phosphorus-nitrogen flame retardant, denoted as MTTP-B.

[0051] Figure 2 (b) The chemical structures of MTTP-B, TPP, and HMT are shown, and these structures were characterized by FTIR spectroscopy. It can be seen that the peak of the benzene ring in TPP appears at 1494 cm⁻¹. -1 and 1595cm -1 The same characteristic peak also appeared in MTTP-B. Furthermore, a peak at 1290 cm⁻¹ was observed in the FTIR spectrum of MTTP-B. -1 The peak at 1022 cm⁻¹ belongs to P=O. -1 and 960cm -1 The peak at 1247 cm⁻¹ is attributed to POC. Furthermore, a peak at 1247 cm⁻¹ was also observed in the FTIR spectrum of MTTP-B. -1 The peak at which CN is attributed to the nitrogen-containing hexagonal triazine ring in HMT is located.

[0052] Figure 2 (c) Demonstrates MTTP-B, TPP, and HMT. 1 ¹H NMR spectra. For the MTTP-B spectrum, the signal in the 7–8.01 ppm range is attributed to hydrogen in the benzene ring, and these signals overlap with those of TPP. For the HMT spectrum, the signal at 4.75 ppm is attributed to the -OH in -CH₂-OH, which does not correspond in the MTTP-B spectrum, indicating that the transesterification reaction has proceeded sufficiently; the signal in the 3.25–3.75 ppm range is attributed to H in N-CH₂-CH₂-O, while the signal in the 2.5–3 ppm range is attributed to H in N-CH₂-N of the hexahydrotriazine ring, and these signals overlap with those of MTTP-B. Figure 2(d) shows the MTTP-B and TPP. 31 The P NMR spectrum shows a signal at -17.25 ppm, which is attributed to P in TPP. After the transesterification reaction, the signal of P in MTTP-B shifts to -11.55 ppm.

[0053] Example 3 The preparation method of the symmetrical phosphorus-nitrogen flame retardant in this embodiment is as follows: Figure 3 As shown in (a), firstly, HMT (10.96 g, 0.050 mol) and TPP (55.47 g, 0.170 mol) were added to a three-necked flask, and 1.4 g of sodium hydroxide (0.035 mol) was added. The mixture was reacted at 180 °C for 2 h to obtain a yellowish-brown liquid. Subsequently, the product was poured into a rotary evaporator and evaporated under reduced pressure at 140 °C for 2 h. By removing small molecules, a clear liquid was obtained, which is the symmetrical phosphorus-nitrogen flame retardant, denoted as MTTP-C.

[0054] Figure 3 (b) The chemical structures of MTTP-C, TPP, and HMT are shown, and these structures were characterized by FTIR spectroscopy. It can be seen that the peak of the benzene ring in TPP appears at 1494 cm⁻¹. -1 and 1595cm -1 The same characteristic peak also appeared in MTTP-C. Furthermore, a peak at 1290 cm⁻¹ was observed in the FTIR spectrum of MTTP-C. -1 The peak at 1022 cm⁻¹ belongs to P=O. -1 and 960cm -1 The peak at 1247 cm⁻¹ is attributed to POC. Furthermore, a peak at 1247 cm⁻¹ was also observed in the FTIR spectrum of MTTP-C. -1 The peak at which CN is attributed to the nitrogen-containing hexagonal triazine ring in HMT is located.

[0055] Figure 3 (c) Demonstrates MTTP-C, TPP, and HMT. 1 ¹H NMR spectra. For the MTTP-C spectrum, the signal in the 7–8.01 ppm range is attributed to hydrogen in the benzene ring, and these signals overlap with those of TPP. For the HMT spectrum, the signal at 4.75 ppm is attributed to the -OH in -CH₂-OH, which does not correspond in the MTTP-C spectrum, indicating that the transesterification reaction has proceeded sufficiently; the signal in the 3.25–3.75 ppm range is attributed to H in N-CH₂-CH₂-O, while the signal in the 2.5–3 ppm range is attributed to H in N-CH₂-N of the hexahydrotriazine ring, and these signals overlap with those of MTTP-C. Figure 3 (d) shows MTTP-C and TPP. 31P NMR spectrum. The signal at -17.25 ppm is attributed to P in TPP. After the transesterification reaction, the signal of P in MTTP-C shifts to -11.55 ppm.

[0056] Example 4 The preparation method of the epoxy resin containing symmetrical phosphorus-nitrogen flame retardants in this embodiment is as follows: EP and MTTP-A are mixed according to the proportions in Table 1, stirred thoroughly at 120°C, and then molten DDM is added; next, the mixture is poured into a preheated mold and placed in a vacuum oven to remove air bubbles; finally, it is cured at 120°C for 2 hours to obtain the epoxy resin composite material. Epoxy resin composite materials containing 1 wt.% and 2 wt.% MTTP-A are named EP / MTTP-1% and EP / MTTP-2%, respectively; epoxy resin without MTTP-A is denoted as EP.

[0057] Table 1 Formulation of epoxy resin composite materials

[0058] The epoxy resins EP / MTTP-1%, EP / MTTP-2%, and EP prepared in Example 4 were characterized and their performance was tested.

[0059] (1) Thermal and dielectric properties: The TGA and DTG curves for EP / MTTP-1%, EP / MTTP-2%, and EP are as follows: Figure 4 As shown in (a), 4(b), and Table 2, EP with added MTTP exhibits similar thermal decomposition behavior to EP. However, increasing the MTTP content leads to higher initial decomposition temperatures (T0) for EP / MTTP1% and EP / MTTP2%. 5% The decrease is slight, attributed to the relatively poor thermal stability of MTTP. It is noteworthy that, compared to EP, the temperature corresponding to the maximum weight loss (T) is lower. max The temperature drop was slight (from 400.6℃ to 395.9℃ or 394.7℃), attributed to the addition of symmetrical phosphorus-nitrogen flame retardants. Furthermore, the maximum weight loss (R0) of EP / MTTP-1% and EP / MTTP-2% was [not specified]. max The carbon content decreased significantly, with EP / MTTP-1% and EP / MTTP-2% decreasing by 33.3% and 26.7%, respectively; in addition, the carbon residue at 800°C increased to 16.9% and 13.1%, respectively. At a loading of 1 wt.%, MTTP catalyzed the carbonization of EP, but when the loading increased to 2 wt.%, the gaseous products generated by excessive decomposition eroded and destroyed the carbon structure.

[0060] Table 2 Thermal analysis data for EP / MTTP -1%, EP / MTTP -2%, and EP

[0061] The DSC test curve is as follows: Figure 4 As shown in (c), all samples exhibit a single glass transition temperature (T). g Furthermore, as the MTTP content increases, T g Elevated. EP / MTTP -1% T g The temperature was 145.7°C, while the T value of EP / MTTP-2% was... g The temperature was 150.4°C, indicating that the increased MTTP content led to enhanced interactions between EP molecular chains, thereby reducing the fluidity of the EP molecular chains.

[0062] Given the critical insulating role of dielectric materials (EP) in modern electronic device packaging, especially in the field of power frequency potting compounds, high dielectric strength, low dielectric loss, and low dielectric constant (ε) are typically required. This invention selected eight samples to measure their electrical breakdown strength and used a two-parameter Weibull distribution to fit the test data. The fitting formula is as follows: P(E) = 1 - ; In the formula, P(E) is the breakdown probability under a certain electric field strength, and E is the measured electrical breakdown field strength; the characteristic parameter α corresponds to the electric field strength when the breakdown probability is 63.2%. The α and β parameters obtained from the breakdown test are listed in Table 3 after calculation. The test results show that MTTP has a significant enhancing effect on the electrical breakdown strength of epoxy resin composites. When the MTTP addition amount is 2wt.%, the Weibull characteristic breakdown field strength α of the epoxy resin composite increases to 306kV / cm, indicating that its high voltage resistance is greatly enhanced, providing a greater safety margin for high voltage insulation design. It is speculated that the reason is the low dielectric constant of the composite material (e.g., Figure 4 (f) shows that the difference in dielectric constant between the unavoidable micro-gaps in the material and the matrix is ​​reduced, thereby alleviating the electric field distortion at the gaps and suppressing the occurrence of partial discharge. As the frequency increases, the dielectric loss shows a trend of first decreasing and then increasing (e.g., Figure 4 (e) shows that different loss mechanisms dominate in different frequency ranges. Overall, the epoxy resin composite with 2 wt.% MTTP has the lowest dielectric loss. This is presumably because MTTP restricts the movement of epoxy resin molecules, and its symmetrical structure effectively reduces dipole relaxation loss and interfacial polarization relaxation loss. This means that the epoxy resin potting compound generates less heat due to dielectric loss during long-term charged operation. The dielectric constant gradually decreases with increasing frequency (e) Figure 4(f) This is because MTTP restricts the orientation movement of polar groups (-OH) in the epoxy resin, and its introduction hardly generates additional molecular or interfacial polarization. More importantly, in the 40-50 Hz frequency range, this epoxy resin composite exhibits low dielectric constant and low dielectric loss, properties that are significant in practical engineering applications, particularly suitable for power equipment and low-frequency electronic devices.

[0063] Table 3 Breakdown Field Strength of EP / MTTP -1%, EP / MTTP -2%, and EP

[0064] (2) Flame resistance Limiting oxygen index (LOI) and vertical burning (UL-94) tests were used to evaluate the flame retardant properties of EP with added MTTP, and the results are as follows: Figure 5 As shown in (a), the pure EP sample exhibited significant flammability, burning intensely and continuously, without a UL-94 rating, accompanied by a large amount of visible black smoke, with an LOI value of 24.0%. After adding MTTP, the LOI value of EP / MTTP-1% reached 28.5%, and it passed the UL-94V-1 rating. EP with only 2wt.% MTTP added achieved the UL-94V-0 rating, demonstrating excellent self-extinguishing performance, with an LOI value as high as 31.5%. With increasing MTTP content, the LOI value and vertical combustion level effectively improved, suggesting that MTTP can play a beneficial role in gas-phase flames. Furthermore, Figure 5 (b) shows a comparison of the LOI value of the EP / MTTP-2% of the present invention with the LOI values ​​of EP containing PN structure flame retardants in the past three years (see references [4]-

[16] ). It can be seen that MTTP makes the LOI value of EP higher at a lower addition level.

[0065] Combustion conditions of EP / MTTP-1%, EP / MTTP-2%, and EP were simulated using CCT. The total heat release (THR) and total smoke production (TSP) curves are shown below. Figure 5 As shown in (c) and 5(d), it is evident that pure EP combustion generates a large amount of heat, with a THR of 121.7 MJ / m³. 2 The addition of MTTP effectively suppressed the total heat release of EP. In EP / MTTP-1% and EP / MTTP-2% solutions, the THR was reduced by 7.2% and 8.7%, respectively, compared to the pure EP sample. Figure 5(f) It can be seen that MTTP effectively suppressed the secondary heat release peak of EP. The smoke generated during combustion is also a key factor affecting the safety of the EP matrix in people's lives. Compared with pure EP, the TSP of EP / MTTP-1% and EP / MTTP-2% decreased by 22.0% and 31.6%, respectively. Furthermore, the addition of MTTP shortened the ignition time (TTI) of EP / MTTP-1% to 65 s and that of EP / MTTP-2% to 67 s (Table 4), indicating that phosphorus-containing MTTP promoted the degradation of EP, which is consistent with... Figure 4 The results from the DTG curves in (b) are consistent. Furthermore, the peak value of the initial thermal release rate (pHRR) of the EP sample containing MTTP increases (e.g., Figure 5 (f) shows that this is also believed to be due to the phosphorus-containing MTTP promoting the degradation of EP. Furthermore, according to... Figure 5 As can be seen from the flue gas production rate (SPR) in (g), both the first and second peak SPRs (pSPR) decreased, indicating that MTTP promoted decomposition in the early stages of combustion. With increasing temperature, MTTP effectively formed a char layer, while simultaneously inhibiting EP combustion and flue gas release. Figure 5 As can be seen in (e), the addition of MTTP caused EP / MTTP-1% and EP / MTTP-2% to decompose more than EP in the early stage. However, as the temperature increased, MTTP effectively formed a carbon layer, reducing mass loss. Figure 5 (h) and (i) show the TSP value and TSP reduction of the EP / MTTP-1% of the present invention compared with the TSP and TSP reduction values ​​of EP of flame retardants containing PN structure in the past three years (see references [4], [5], [8], [9],

[12] ,

[16] ,

[17] ,

[18] ). It can be seen that MTTP achieves excellent smoke suppression effect with a small amount of addition.

[0066] In addition, the carbon residue of EP / MTTP-1% and EP / MTTP-2% increased to 10.3 wt.% and 8.1 wt.%, respectively, and the average effective heat of combustion (Av-EHC) of EP / MTTP-1% and EP / MTTP-2% increased to 33.1 MJ / kg and 33.9 MJ / kg, respectively (Table 4), which is mainly due to the condensed phase effect of MTTP.

[0067] Table 4. CCT Results for EP / MTTP -1%, EP / MTTP -2%, and EP

[0068] Figure 6Digital photographs and SEM images of EP / MTTP-1%, EP / MTTP-2%, and EP after CCT are presented. It can be seen that there is almost no residual carbon in EP after CCT (e.g., Figure 6 (a) and (a') show the residual char content, which is only 4.7 wt.% (Table 4). After the addition of MTTP, expanded char is clearly observed. The char height increases to 18 mm with EP / MTTP-1% (e.g., ...). Figure 6 (b) shows that the carbon surface has many wrinkles (as shown in the image). Figure 6 (b') shows). The EP / MTTP-2% char height reaches 30mm (as shown). Figure 6 (c) shown), but the carbon surface has obvious cracks (as shown). Figure 6 (as shown in (c')). Figure 6 (a''), 6 (a'''), 6 (b''), 6 (b'''), 6 (c''), 6 (c''') show the microscopic appearance of CCT residual carbon using SEM. Figure 6 (b'') and 6 (b''') show that the expanded char layer formed after combustion of EP / MTTP-1% is composed of stacked residual char fragments. The residual char of EP / MTTP-2% is relatively continuous, but still exhibits obvious cracks, and the stacking of residual char fragments is minimal (e.g., Figure 6 (c''), 6 (c''') are shown).

[0069] In addition, XPS analysis was performed on the carbon residue after CCT for EP and EP / MTTP-1%, and the results are as follows: Figure 7 (a)-7(g) are shown. The results show that the char residue of EP / MTTP-1% contains, in addition to the C, N and O elements found in pure EP, P ( Figure 7 (b) Further examination of the P2p spectrum revealed a singlet associated with P=O and POC, indicating the presence of polyphosphates and pyrophosphates in the carbon residue. These acidic substances significantly contribute to promoting the dehydration and carbonization processes in the EP matrix. The peaks detected in the C1s spectrum at 284.8 eV, 285.7 eV, and 287.8 eV correspond to C-C, CO, and C=O bonds, respectively (e.g., ...). Figure 7 (c) is shown), attributed to the framework structure in the carbon layer. In the N1s spectrum (as shown in...), Figure 7 In (d) shown, the peaks at 398.1 eV and 399.7 eV correspond to CN and NH bonds, respectively, and these peaks originate from the curing agent DDM. In the C1s spectrum of EP / MTTP-2% (as shown in [reference]... Figure 7 In (e) shown, a CN bond appears at 285.4 eV, which is not present in carbon from pure EP. The N1s spectrum of EP / MTTP-2% (as shown) Figure 7 (f) shown) and the N1s spectrum of EP (as shown) Figure 7The difference (as shown in (d)) is not significant; the CN and NH bonds originate from the curing agent DDM. The P2p spectrum of EP / MTTP-2% (as shown in (d)) is similar. Figure 7 (g) illustrates the locations of P=O and POC. The triazine ring derivative in MTTP is incorporated into the char layer via CN bonds. XPS results for EP / MTTP-2% effectively demonstrate the synergistic effect of P / N flame retardants on epoxy resin in the condensed phase.

[0070] To investigate the thermal decomposition characteristics of EP / MTTP-1%, EP / MTTP-2%, and EP in the gas phase, their pyrolysis process in a nitrogen atmosphere was analyzed by TG-FTIR. Figure 8 Figures (a) and (b) show the TG-FTIR thermograms of EP and EP / MTTP-2% samples, respectively. It can be seen that the pyrolysis gas concentration of the EP / MTTP-2% sample is much lower than that of pure EP. The FTIR spectra of the pyrolysis products at different temperatures are shown below. Figure 8 As shown in (c) and 8(d), the spectroscopic results indicate that water (3750 cm⁻¹) was produced during the thermal decomposition of EP and EP / MTTP-2%. -1 ), CH compounds (2970cm) -1 ), CO2 (2360cm) -1 ), aromatic compounds (1609cm) -1 1508cm -1 826cm -1 748cm -1 ) and ether (1176cm) -1 It is worth noting that at 400℃, the EP / MTTP-2% sample showed a temperature range of 1150-1300 cm⁻¹. -1 The absorption peak intensity in this range is significantly higher than that of pure EP, mainly due to the PO (1175 cm⁻¹) produced by the decomposition of MTTP. -1 ) and P=O (1256cm) -1 The superposition of bond vibration peaks. Furthermore, the absorption peak intensities of aromatic compounds and hydrocarbons produced by the pyrolysis of EP / MTTP-2% are lower than those of pure EP, indicating that MTTP inhibits the formation of various flue gases during EP combustion. The intensity-time curves of aromatic compounds, carboxyl groups, carbon monoxide, carbon dioxide, and hydrocarbons in the gaseous products of EP and EP / MTTP-2% are shown below. Figure 8 As shown in (e)-8(i). Compared to EP, EP / MTTP - 2% of hydrocarbons (such as Figure 8 (i) shown), carbonyl groups generated by ether bond cleavage and oxidation (such as Figure 8 (f) as shown) and aromatic compounds (such as Figure 8The release of EP (as shown in (e)) increased, but the total amount decreased significantly. This indicates that MTTP promoted the premature decomposition of EP, generating hydrocarbons, carbonyl compounds, and aromatic compounds, while reducing the formation of these decomposition products. Figure 8 (h) It can be seen that the CO2 release of pure EP is divided into two stages: the first stage occurs between 1000-1500 s, with a temperature range of 360-530 °C, corresponding to the thermal decomposition and oxidation of the EP backbone; the second stage begins at 1700 s, when the temperature exceeds 600 °C, due to the gas-solid heterogeneous oxidation reaction between the carbon layer and oxygen at high temperatures. In contrast, EP / MTTP-2% shows only a weak CO2 release peak between 1250 s and 1750 s, indicating that the oxidation of the EP backbone is weakened due to the presence of MTTP. TG-FTIR analysis confirms that the introduction of MTTP significantly reduces the generation of combustible small molecule gases.

[0071] In summary, MTTP exerts multiple flame-retardant effects in both the gas and condensed phases through a phosphorus-nitrogen synergistic effect. In the condensed phase, MTTP undergoes thermal decomposition to form polyphosphoric acid, catalyzing the dehydration of EP to generate char. The hexahydrotriazine ring in MTTP integrates into the char layer, forming a thermally stable CN structure. In the gas phase, MTTP decomposes to generate phosphorus-containing free radicals such as PO·, which effectively capture H· and HO· free radicals in the combustion chain reaction and interrupt it. Simultaneously, the nitrogen-containing products released from the decomposition of triazine also hinder gas-phase combustion. Under the synergistic effect of phosphorus and nitrogen, EP / MTTP-1% and EP / MTTP-2% exhibit excellent flame-retardant properties.

[0072] (3) Mechanical properties The mechanical properties of EP / MTTP-1%, EP / MTTP-2%, and EP were tested, and the results are as follows: Figure 9 As shown in (a)-9(c), MTTP significantly enhances the flexural and tensile properties of EP. Specifically, when the MTTP content increases to 2 wt.%, the flexural strength and tensile strength of EP increase to 96.9 MPa and 58.0 MPa, respectively, representing increases of 8.6% and 33.6% compared to pure EP. The elongation at break of the EP / MTTP-1% and EP / MTTP-2% samples increased from 1.5% of pure EP to 2.8% and 5.5%, respectively, with a tensile toughness as high as 86.7%. The EP / MTTP-2% sample exhibits significant improvements in both strength and toughness. The peel strength of EP is crucial for electronic packaging, playing a core role in component fixation and performance stability. Figure 9As shown in (c), the average peel force of pure EP was 11.7 N, and the average peel strength was 469.6 N / m. The average peel force and average peel strength decreased slightly after adding 1 wt.% MTTP. After adding 2 wt.% MTTP, the average peel force and average peel strength increased to 12.5 N and 498.8 N / m, respectively, representing increases of 6.2% and 6.3% compared to pure EP. A trade-off exists between the π-π stacking interactions formed by the benzene ring and triazine ring in MTTP and the EP molecular chain and the original EP molecular chain.

[0073] To elucidate the enhancement of the mechanical properties of EP / MTTP composites, this invention employs molecular dynamics (MD) simulations to study their structural and interaction characteristics. The radial distribution function (RDF) is a powerful tool for characterizing the spatial distribution probability of particles. In hydrogen bond analysis, the RDF between donor and acceptor atoms typically exhibits a distinct peak at 2-3 Å, and the integral area under this peak is directly related to the number of hydrogen bonds in the system. Figure 9 As shown in (f), the RDF peak intensity at 2.5 Å for EP / MTTP-1% and EP / MTTP-2% is higher than that for pure EP, strongly indicating the formation of stable hydrogen bonds between MTTP and EP. Among them, EP / MTTP-2% shows the highest peak at 2.5 Å, indicating that this system has the largest number of hydrogen bonds. These hydrogen bonds mainly originate from the electrostatic interaction between the hydroxyl hydrogen atoms on the EP chain and the oxygen atoms in the P=O group or the nitrogen atoms in MTTP.

[0074] The equilibrium cohesive energy density (CED) of each system (e.g.) Figure 9 (d) has been calculated. Figure 9 As shown in (d), the CED value increases with the increase of MTTP content, reaching 3.221 × 10⁻⁶ for the EP / MTTP-2% sample. 8 J / m 3 This indicates a strong interfacial bond between MTTP and the EP molecular chain. Meanwhile, as... Figure 9 As shown in (e), the mean square displacement (MSD) of both composite materials is significantly lower than that of pure EP, reflecting a marked decrease in the mobility of molecular chain segments and an increase in molecular packing density. These results are also consistent with the higher glass transition temperature (T0) of the EP / MTTP-2% sample. g (Same as above)

[0075] Figure 9(g)-9(i) shows SEM images of the fracture surfaces after tensile tests of EP, EP / MTTP-1%, and EP / MTTP-2%. It can be seen that the fracture surface of pure EP is smooth, a characteristic of typical brittle fracture. In contrast, the fracture surface of the EP / MTTP composite exhibits a large number of uniformly distributed microcracks, which play a crucial role in energy absorption and inhibiting crack propagation. The rigid structure of MTTP particles acts as microscale stress concentration points within the EP matrix. Overall, the improvement in mechanical properties is attributed to two key factors: first, the MTTP molecules containing multiple rigid benzene ring units enhance π-π stacking, increasing the interaction between MTTP and EP, and absorbing energy upon external impact; second, MTTP acts like a "fishing net," absorbing energy and increasing toughness through deformation under external forces.

[0076] (4) Hydrophobicity and transparency The hydrophobicity of epoxy resins is crucial in their application as electronic packaging materials. Photographs of the water contact angles of EP, EP / MTTP-1%, and EP / MTTP-2% are shown below. Figure 10 As shown in (a)-10(c), Figure 10 (d) shows the results for the water contact angle: 77.98° for pure EP, 78.25° for EP / MTTP-1%, and 79.81° for EP / MTTP-2%. The addition of MTTP resulted in a tighter bond between the EP molecular chains, which was also demonstrated by… Figure 9 The CED in (d) is explained.

[0077] The long-term transparency of EP / MTTP composite materials allows for clear visibility of the internal structure of electronic components, facilitating subsequent troubleshooting and condition monitoring without disassembling and damaging the product. For example... Figure 10 As shown in (e)-10(g), it can be clearly seen that the addition of MTTP affects the color of the EP composite material, and the greater the amount added, the more yellow the color of the EP / MTTP composite material, but the background is still visible through the EP / MTTP composite material.

[0078] The prior art references mentioned in the embodiments of the present invention are as follows: [4] Y. Gou, Y.F. Zha, D.X. Sun, J.H. Yang, Y. Wang. Synchronouslyenhanced flame-retardance and mechanical properties of epoxy resin via a P / N-containing active curing agent. Polym. 335 (2025) 128827. https: / / doi.org / 10.1016 / j.polymer.2025.128827. [5] X.F. Shi, F. Shi, C.Z. Luo, C.H. Zhang, L. Shang. Bio-basedphosphorus multifunctional P / N flame retardant to improve synergistically themechanical and fire resistance of epoxy resin. Mater. Today. Chem. 46 (2025)102755. https: / / doi.org / 10.1016 / j.mtchem.2025.102755. [6] Y.B. Zou, Z.H. Shi, J.J. Shi, F.B. Luo, H.Z. Li. 'Honeycomb-like'triazine-based covalent organic framework derivative for remarkably improvingboth flame retardancy and mechanical properties of epoxy resin. Constr.Build. Mater. 426 (2024) 136166. https: / / doi.org / 10.1016 / j.conbuildmat.2024.136166. [7] P.L Zheng, H.H.Zhao, Y.W. Meng, J.W. Li, Q.Z. You, Q.Y. Liu.Melamine-based biomass-containing P / N synergistic flame retardants confersuperb flame retardancy and toughness to epoxy resins. Prog. Org. Coat. 198(2024) 108927. https: / / doi.org / 10.1016 / j.porgcoat.2024.108927. [8] H. Zhang, Y.Y. Peng, Y.H. Xiao, S. Kong, X.W. He, L.N. Liu, G.B.Lou, Y. Kuang, S.Y. Fu, Q.Q. Rao. A novel multifunctional phosphorous andnitrogenous reactive flame retardant toward epoxy resins by one-pot method.J. Appl. Polym. Sci. 141(6) (2023) e54929. https: / / doi.org / 10.1002 / app.54929. [9] P.L. Zheng, H.H. Zhao, Q.Y. Liu. P / N synergistic integrated flameretardants with instant cross-linking at high-temperature for flameretardancy and impact resistance of epoxy resins. Polym. Degrad. Stab. 225(2024) 110817. https: / / doi.org / 10.1016 / j.polymdegradstab.2024.110817.

[10] Y.B. Zou, K. Niu, Y.B. Li, X.Y. Yang, Z.H. Shi, F.B. Luo, H.Z.Li. A novel P / N synergistic hydrogen-bonded organic framework for improvingflame retardancy of epoxy resin.Constr. Build. Mater. 490 (2025)142606.https: / / doi.org / 10.1016 / j.conbuildmat.2025.142606

[11] Y. Zhao, S. He, C.B. Yu, S.Y. Shi, W.H. Rao. Quercetin-inspiredflame retardant for transparent and mechanically robust epoxy resins withenhanced fire safety. Sustain. Mater. Technol. 45 (2025) e01575. https: / / doi.org / 10.1016 / j.susmat.2025.e01575.

[12] W. Wang, Y. Liu, Q. Wang. Synthesis of melamine cyanuric basedflame retardant via hydrogen bond self-assembly and in-situ dispersionstrategies for improving comprehensive performance of epoxy resin. Compos.Part. A-Appl. S. 176 (2023) 107826. https: / / doi.org / 10.1016 / j.compositesa.2023.107826

[13] Q.X. Huang, X.Y. Shan, Y.X. Diao, B.Y. Hou, J.C. Li, L.Z. Wang.Synthesis of novel bio‐based schiff base flame retardant to improve the firesafety of epoxy resin. J. Appl. Polym. Sci. 142(32) (2025) e57280. https: / / doi.org / 10.1002 / app.57280.

[14] Z.K. Wang, Y.F. Xiao, S.G. Wu, Z. Qin, Y.Z. Wang, L. Chen.Topology-engineered semi-crosslinked phosphaphenanthrene architectures forepoxy resins: Unlocking synergistic flame retardancy, mechanical, anddielectric properties. Chem. Eng. J. 519 (2025) 165455. https: / / doi.org / 10.1016 / j.cej.2025.165455

[15] J.X. Ren, G.C. Yang, X.C. Deng, S.C. Huang, C.F. Lu. ATryptamine-based DOPO Derivative as a Flame Retardant for Epoxy Resins.Polym. Degrad. Stab. 218 (2023) 110595. https: / / doi.org / 10.1016 / j.polymdegradstab.2023.110595.

[16] H.J. Duan, Y. Li, C.T. Liu, J. Kang, J. Zhang, Y. Gao, Y. Chen,W.P. Liu. Well-designed flame retardants for epoxy resin composites thatsimultaneously improve heat resistance, mechanical properties and firesafety. Mater. Today. Commun. 39 (2024) 109421. https: / / doi.org / 10.1016 / j.mtcomm.2024.109421.

[17] P.F. Liu, X. Wang, J.Z. Huang, X.W. Jiang. Halogen-free epoxyflame retardant&promoter with diimidazole skeleton improves overallproperties of epoxy resins. Chem. Eng. J. 498 (2024) 155408. https: / / doi.org / 10.1016 / j.cej.2024.155408.

[18] J.Y. Lu, L.P. Chen, Z.L. Luo, B.B. Wang. A vanillin-containingDOPO-based compound for improving the flame retardancy of epoxy resinsimultaneously with comparable transparency and mechanical property. J. Appl.Polym. Sci. 140(9) (2022) e53556. https: / / doi.org / 10.1002 / app.53556。

Claims

1. A method for preparing epoxy resin containing symmetrical phosphorus-nitrogen flame retardants, characterized in that, An epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant is obtained by mixing and curing epoxy resin, a symmetrical phosphorus-nitrogen flame retardant, and a curing agent. The preparation method of the symmetrical phosphorus-nitrogen flame retardant is as follows: hexahydro-1,3,5-tris(hydroxyethyl)-s-triazine, triphenyl phosphate, and a catalyst are reacted at 140-180℃ for 2-5 hours, and the product is distilled under reduced pressure to obtain the symmetrical phosphorus-nitrogen flame retardant. The specific operation process for preparing the epoxy resin containing the symmetrical phosphorus-nitrogen flame retardant is as follows: epoxy resin and the symmetrical phosphorus-nitrogen flame retardant are mixed and stirred at 100-140℃, then a curing agent is added to obtain a mixture. The mixture is poured into a preheated mold and placed in a vacuum oven to remove air bubbles. It is then cured at 110-160℃ for 2-4 hours to obtain the epoxy resin containing the symmetrical phosphorus-nitrogen flame retardant.

2. The method for preparing epoxy resin containing symmetrical phosphorus-nitrogen flame retardants as described in claim 1, characterized in that, The curing agent is 4,4'-diaminodiphenylmethane.

3. The method for preparing epoxy resin containing symmetrical phosphorus-nitrogen flame retardants as described in claim 1, characterized in that, The epoxy resin accounts for 78.4-79.2% of the total mass of the raw materials, the symmetrical phosphorus-nitrogen flame retardant accounts for 1-2% of the total mass of the raw materials, and the curing agent accounts for 19.6-19.8% of the total mass of the raw materials.

4. The method for preparing epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant as described in claim 1, characterized in that, The catalyst is sodium hydroxide.

5. The method for preparing epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant as described in claim 1, characterized in that, The molar ratio of hexahydro-1,3,5-tris(hydroxyethyl)-s-triazine, triphenyl phosphate, and catalyst is (0.03-0.06):(0.14-0.18):(0.02-0.05).

6. The method for preparing epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant as described in claim 1, characterized in that, The vacuum distillation temperature is 140-180℃, and the time is 2-6 hours.

7. An epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant, characterized in that, The epoxy resin containing a symmetrical phosphorus-nitrogen flame retardant as described in any one of claims 1-6 was prepared.

Citation Information

Patent Citations

  • Flame-retardant triazine active ester curing agent, epoxy resin composition for copper-clad plate and preparation method

    CN110790900A